Ideologi Gerakan Politik Islam Di Indonesia - Basyir, Kunawi (IAIN Ponorogo, 2016)
Abstract: Entering to modern era constitutes one big challenge in which beside it is considered as a resurrection era through which it is fully engaged with religious thoughts, social conflict happened in many places is also suspected as another factor coming along with it. Thought religion is not the only factor, but religious thought plays important role with the result that the world comes into ongoing critical period. They have arrived to primordial solidarity area which constitutes the weak point of the life of the nation. The royalty of religious followers toward their religion in negative ways tend to bear such exclusive ideology which produces internal conflict among interreligious people. As Indonesia todayâ€™s condition, different understanding and religious practice become a big trouble which is hard to unite so that it causes unforthcoming political flames. Fundamental problem about that is a problem related to different understandings toward state and religion relationship. In one hand, it said that religion constitutes part of state but in other hand, both religion and state are different instead of undivided things. Looking at such phenomenon, this writing will try to read and to analyze the ideology of Islamic political movement in Indonesia since old order, new order and post reformation. Ø§Ù„Ù…Ù„Ø®Øµ: Ø¸Ù‡Ø±Øª Ø§Ù„Ù†Ù‡Ø¶Ø© Ø§Ù„ÙÙƒØ±ÙŠØ© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ù…Ø¹ Ø£Ù„ÙˆØ§Ù† Ø§Ù„ØªØµØ§Ø¯Ù… Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ ÙÙŠ Ø§Ù„Ù‚Ø±Ù† Ø§Ù„ØØ¯ÙŠØ« ÙÙŠ Ø£ÙŠ Ù…ÙƒØ§Ù†. ÙˆØ§Ù„Ø¯ÙŠÙ† Ù„ÙŠØ³ Ø¹Ø§Ù…Ù„Ø§ ÙˆØ§ØØ¯Ø§ Ø§Ù„Ø°ÙŠ ÙŠØ³Ø§Ø¹Ø¯ Ø¹Ù„ÙŠ Ø§Ù„Ø¯ÙˆØ± Ø§Ù„ÙÙƒØ±ÙŠ Ø§Ù„Ø¯ÙŠÙ†ÙŠ ØØªÙ‰ Ø¨Ø¯Ø£ Ø§Ù„Ø¹Ø§Ù„Ù… ÙŠØ¯Ø®Ù„ ÙÙŠ Ø§Ù„Ø£Ø²Ù…Ø© Ø§Ù„Ù…Ø³ØªÙ…Ø±Ø©. Ø¨Ø¯Ø£ Ø§Ù„Ù†Ø§Ø³ ÙŠØ¹Ø±ÙÙˆÙ† ÙÙŠ Ø§Ù„Ø¬Ø§Ù†Ø¨ Ø§Ù„ØªØ³Ø§Ù…ØÙŠ Ø§Ù„Ø¨Ø¯Ø§Ø¦ÙŠ Ø§Ù„Ø°ÙŠ ÙŠÙƒÙˆÙ† Ù†Ù‚Ø·Ø© Ø¶Ø¹ÙŠÙØ© ÙÙŠ Ø§Ù„ØÙŠØ§Ø© Ø§Ù„Ø¯ÙˆÙ„ÙŠØ© ÙˆØ§Ù„ÙˆØ·Ù†ÙŠØ©. Ø§Ù„ØªØ¹ØµØ¨ ÙÙŠ Ø·Ø§Ø¹Ø© Ø§Ù„Ø£Ù…Ø© Ø¹Ù„ÙŠ Ø¯ÙŠÙ†Ù‡Ø§ Ø³Ù„ÙŠØ¨Ø§ ÙŠØ¸Ù‡Ø± Ø§Ù„Ø¥ÙŠØ¯ÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„Ù…ØºÙ„Ù‚Ø© Ø§Ù„ØªÙŠ ØªÙˆÙ„Ø¯ Ø§Ù„ØªØ¹Ø§Ø±Ø¶ Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠ ÙˆØ§Ù„ØªØ²Ø¹Ø© Ø¨ÙŠÙ† Ø§Ù„Ø£Ù…Ø© Ø§Ù„Ù…ØªØ¯ÙŠÙ†Ø© ÙƒÙ…Ø§ Ù‚Ø¯ ÙˆÙ‚Ø¹Øª ÙÙŠ Ø£Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ Ø§Ù„Ù…Ø®Ø§Ù„ÙØ© ÙÙŠ Ø§Ù„ØªÙØ§Ù‡Ù… ÙˆØ§Ù„Ø¹Ù…Ù„ÙŠØ© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© ØªØµÙŠØ± Ù…Ø³Ø¦Ù„Ø© ØµØ¹Ø¨Ø© ÙÙŠ ØªÙˆØØ¯Ù‡Ù… Ø¨Ù„ ØªØ¹Ø±Ø¶ Ø§Ù„Ù…ØªÙ‡ÙŠØ¬ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ Ø§Ù„Ù…Ø³ØªÙ…Ø±ÙŠ. Ø§Ù„Ù…Ø³Ø¦Ù„Ø© Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© Ù‡ÙŠ Ø§Ù„Ù…Ø®Ø§Ù„ÙØ© ÙÙŠ Ø§Ù„ØªÙÙ‡Ù… Ø¹Ù„ÙŠ Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ø¯ÙŠÙ† ÙˆØ§Ù„Ø¯ÙˆÙ„Ø©. ÙˆÙÙŠ Ø§Ù„Ø¬Ø§Ù†Ø¨ØŒ Ø£Ù† Ø§Ù„Ø¯ÙŠÙ† Ù‡Ùˆ Ù…Ù† Ø§Ù„Ø¯ÙˆÙ„Ø© ÙˆØ§Ù„Ø¢Ø®Ø±Â Ø£Ù† Ø§Ù„Ø¯ÙŠÙ† Ù…Ø®Ø§Ù„Ù Ø¨Ø§Ù„Ø¯ÙˆÙ„Ø© ÙˆÙ„ÙƒÙ†Ù‡ Ù„Ø§ ÙŠØªØ¬Ø²Ø£ Ù…Ù†Ù‡Ø§. Ù†Ø¸Ø±Ø§ Ø¹Ù„ÙŠ Ù‡Ø° Ø§Ù„Ù‚Ø¶Ø§ÙŠØ§ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© ØªØ¨ØØ« ÙˆØªØÙ„Ù„ Ø¹Ù„ÙŠ Ø¥ÙŠØ¯Ù„ÙˆØ¬ÙŠØ© Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ø³ÙŠØ§Ø³ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ Ø£Ù†Ø¯ÙˆÙ†Ø³ÙŠØ§ Ù…Ù†Ø° Ø¹ØµØ± Ø§Ù„Ø¬Ù…Ù‡ÙˆØ± Ø§Ù„Ù‚Ø¯ÙŠÙ… ÙˆØ§Ù„Ø¬Ø¯ÙŠØ¯ ÙˆØ¹ØµØ± Ø§Ù„Ø¬Ù…Ù‡ÙˆØ± Ø¹Ù‚Ø¨ Ø§Ù„Ø¥ØµÙ„Ø§Ø.Abstrak: Memasuki abad modern merupakan era kebangkitan pemikiran keagamaan yang dibarengi dengan maraknya konflik sosial di mana-mana. Walaupun agama bukan satu-satunya faktor utama, dalam eskalasinya pemikiran keagamaan memainkan peranan penting sehingga dunia mulai memasuki periode krisis yang berlangsung secara terus-menerus, mereka sudah mulai masuk pada wilayah solidaritas primordial yang merupakan titik lemah dari kehidupan berbangsa dan bernegara. Kesetiaan umat terhadap agamanya secara negatif cenderung melahirkan ideologi eksklusif yang dapat melahirkan konflik intern dan antarumat beragama. Sebagaimana yang terjadi di Indonesia perbedaan pemahaman dan praktik keagamaan menjadi persoalan yang sulit untuk dipersatukan sehingga menimbulkan gejolak politik yang tidak kunjung datang. Persoalan yang mendasar dalam hal ini adalah masalah perbedaan pemahaman terhadap hubunganÂ agama dan negara, Satu sisi memandang bahwa agama meupakan bagian dari negara, sedang satu sisi memandang bahwa antara agama dan negara adalah berbeda tetapi keduanya tidak bisa dipisahkan. Melihat fenomena ini maka tulisan ini akan membaca dan menganalisis ideologi gerakan politik Islam di Indonesia sejak Orde Lama, Orde Baru, dan pasca reformasi.